2007
DOI: 10.1143/jjap.46.4642
|View full text |Cite
|
Sign up to set email alerts
|

Film Bulk Acoustic Resonator using High-Acoustic-Impedance Electrodes

Abstract: We report new high-resolution photoabsorption data on the Lyman bands of H, obtained with a sample at very low vapour density and rather low temperature. The measurements were carried out by synchrotron spectroscopy, using the continuum emitted by the 500 MeV accelerator of the Physikalisches Institut in Bonn. Spectra were recorded in the first order of a 6000 line/" holographic grating, at a dispersion of 0.6 A mm-'.More complete photoabsorption data than previously available for the bands from (0,O) to (9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Many research works have studied the effects of various electrode materials, including Pt [ 67 ], Mo [ 66 , 68 ], W [ 69 ], Ru [ 70 , 71 ], Ir [ 72 , 73 , 74 ], Ta [ 75 ], Al/Au/Cu [ 76 ], CNT (carbon nanotube) [ 77 ], graphene [ 78 , 79 ], and ITO (indium tin oxide) [ 80 ]. Among them, Mo, W, Ru, and Ir have high Young’s modulus, but the density of W is relatively high.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many research works have studied the effects of various electrode materials, including Pt [ 67 ], Mo [ 66 , 68 ], W [ 69 ], Ru [ 70 , 71 ], Ir [ 72 , 73 , 74 ], Ta [ 75 ], Al/Au/Cu [ 76 ], CNT (carbon nanotube) [ 77 ], graphene [ 78 , 79 ], and ITO (indium tin oxide) [ 80 ]. Among them, Mo, W, Ru, and Ir have high Young’s modulus, but the density of W is relatively high.…”
Section: Methodsmentioning
confidence: 99%
“…Masanori et al further studied the effect of Young’s modulus E and density ρ on k eff 2 ( ) [ 71 ]. It was found that when the ρ is fixed, k eff 2 increases with the increase of the electrode Z ( E increases) ( Figure 10 b), and when the E is fixed, the k eff 2 changes slightly as the electrode Z increases ( ρ increases) ( Figure 10 c).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The materials considered in this calculation are Mo, Ru, Rh, W and TiN. Mo and Ru are widely used as an electrode for FEARs [6][7][8][9]. The material parameters are shown in Table 1.…”
Section: Materials Of Electrodesmentioning
confidence: 99%